2019
DOI: 10.1111/pirs.12372
|View full text |Cite
|
Sign up to set email alerts
|

Territorial determinants and NUTS 3 regional performance: A spatial analysis for Italy across the crisis

Abstract: This paper analyses the differential impact of several territorial determinants of the economic performance of Italian provinces (NUTS 3 level). as measured by per capita GDP, export and employment growth from 1999 to 2014. It covers both the pre‐crisis and the crisis period and stresses the role of geographical proximity in shaping local performance over a wide set of explanatory variables. In order to do so, we employ, firstly, a spatial Durbin model which enables us to discriminate between direct and indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 83 publications
(101 reference statements)
0
13
0
Order By: Relevance
“…Other studies undertake their analyses using cost functions (Morrison & Schwartz, ; Nadiri & Mamuneas, ). Some recent contributions to this question have employed different theoretical frameworks to capture the spatial externalities of transport infrastructure (Chen & Haynes, ; Cohen, ; Crescenzi & Rodríguez‐Pose, ; Del Bo & Florio, ; Lo Cascio, Mazzola, & Epifanio, ; Yu, De Jong, Storm, & Mi, ). In general, their results point (albeit not unanimously) to a direct and positive impact.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies undertake their analyses using cost functions (Morrison & Schwartz, ; Nadiri & Mamuneas, ). Some recent contributions to this question have employed different theoretical frameworks to capture the spatial externalities of transport infrastructure (Chen & Haynes, ; Cohen, ; Crescenzi & Rodríguez‐Pose, ; Del Bo & Florio, ; Lo Cascio, Mazzola, & Epifanio, ; Yu, De Jong, Storm, & Mi, ). In general, their results point (albeit not unanimously) to a direct and positive impact.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With only a few exceptions (Arbués et al, ; Chen & Haynes, ; Lo Cascio et al, ), the analysis is made without any prior disaggregation by type of infrastructure. In this regard, different studies have found a positive impact from a specific transportation mode on some measure of the regional or urban economic performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, a recent study by Crescenzi and Rodriguez‐Pose () finds that neither having a good endowment of roads, nor being surrounded by regions with good transport infrastructure (proxied by regional motorways) has a significant impact on regional economic growth. In line with these findings, Lo Cascio et al () also find that traditional factors of growth (such as road infrastructure endowment) have lost relevance during the crisis period. Therefore, we believe that the impact of infrastructures may be non‐linear since it is possible that once a minimum threshold of basic transport infrastructures has been achieved, the direct contribution to growth of more “traditional” infrastructure endowments may tend to decrease and more general accessibility concepts should be considered.…”
Section: Resultsmentioning
confidence: 68%
“…Crescenzi, Luca, and Milio () looked at several macroeconomic and regional factors that may have affected regional resilience in Europe. Instead, Fratesi and Perucca (), Mazzola, Lo Cascio, Epifanio, and Di Giacomo () and Lo Cascio, Mazzola, and Epifanio () claimed that several dimensions of the territorial capital acted as relevant determinants of the provincial (NUTS 3 regions) ability to afford periods of distress. Conversely, according to Rios (), national factors (i.e., labour market institutions) assumed a greater importance than local endogenous one in explaining increasing unemployment disparities in European regions after the crisis.…”
Section: Regional Competitiveness and Economic Resiliencementioning
confidence: 99%
“…In addition, relevant studies have shown that labour conditions (Ríos, 2017) and human capital endowment (Lo Cascio, Mazzola, & Epifanio, 2018) represent an important determinant of different regional impact of the last great economic crisis (Ubago, García-Lautre, Iraizoz, & Pascual, 2019) and with profound, specific and complex reflection on key socio-economic regional phenomena.…”
mentioning
confidence: 99%